Quality Improvement and Market Diversification of Honey Bee and Herbal Based Products in Herbal Propolis Mouthwash - Hendrawati, Tri Yuni; Nugrahani, Ratri Ariatmi; Hasyim, Ummul Habibah; Puteri, Renty Anugerah Mahaji; Permatasari, Tria Astika Endah; Darto, Darto; Andriansyah, Miftah; Wusono, Ciska Nabilla; Hidayat, Sri (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2023)
In the 2023 Kedaireka matching fund grant activity with the title pimproving the quality and market diversification of honey bee and herbal based products Scheme Downstreaming innovation from research results for commercialization purposes, innovation has been carried out in the production of herbal propolis mouthwash. In the herbal propolis mouthwash innovation, a formula was combined on the function of propolis and the results of betel leaf extraction for a non-alcoholic mouthwash formula. The prototype of this mouthwash has received a distribution permit from BPOM NA with number NA 18231400102 using the Prolizama brand. This activity is a collaboration between Universitas Muhammadiyah Jakarta and partner CV Madu Apiari Mutiara in Depok, West Java, Indonesia. In this activity, the activities carried out include making prototypes, testing, packaging design, processing BPOM NA distribution permit certification, limited scale production, optimizing online marketing via the website and making a business plan for the UMJ and CV Madu Apiari Mutiara agreement, Madu Apiari Mutiara. Innovation Herbal propolis mouthwash with natural composition, high antioxidant and anti-inflammatory in combination with propolis and betel herbs. In achieving a price competitive product, it is hoped that it will be a substitute for propolis mouthwash imported from Japan without expensive herbs. This formula is being patented. The production of herbal propolis mouthwash is expected to increase partner income. In the implementation of independent learning, the MKBM independent campus is the fulfillment of IKU 2, Students Gain Experience Outside Campus, IKU 3, namely Lecturers Doing Activities Outside Campus and IKU 5, Lecturers' Work Results are Used by the Community. The Depok City Regional Government and the community will have superior products, herbal jelly candy and herbal propolis mouthwash that are healthy and halal. A significant impact for UMJ is an increase in the entrepreneurial atmosphere for lecturers and students.